Effects of tea (Camellia Sinensis) on antioxidant potential and fermentation characteristics of yogurt / Premalatha A/P Muniandy - Muniandy, Premalatha (2014)

(untitled)
The present study investigated the effects of green, white and black tea (Camellia sinensis; 2% w/v) on the fermentation of milk and antioxidant potential of yogurt. Each tea (water extract) was added into milk-starter culture mixture and incubation was carried out at 42°C until pH was reduced to 4.5. The yogurts were then refrigerated (4°C) for up to 21 days and samples were analysed for antioxidant potential (diphenyl picrylhydrazyl (DPPH) radical scavenging, ferric reducing antioxidant power (FRAP) and ferrous ion chelating (FIC) assays), pH, titratable acid and viable yogurt bacteria counts. Tea yogurts had higher antioxidant potentials (p < 0.05) than plain yogurt with green tea yogurt (GTY) having the highest FRAP (2.49 - 2.98 mmol Fe2+ E/L) and black tea yogurt (BTY) having the highest FIC (87.50 - 89.87 %) activity throughout the storage period. Both GTY (90.07 - 96.74%) and white tea yogurt (WTY; 89.83 - 96.39%) showed the highest DPPH radical scavenging activity throughout the storage period. The presence of green and black tea water extracts prolonged the milk fermentation time (>270 minutes and 240 minutes respectively) to pH 4.5 compared to control (180 minutes). The pH of tea yogurts during refrigerated storage (pH 4.33 - 4.53) was similar to control (pH 4.28 - 4.41) but greater acid production was observed in all tea yogurts (0.78 - 0.99% lactic acid equivalent; LAE) compared to plain yogurts (0.70 - 0.91% LAE). Highest acid content was found in WTY yogurt at the end of fermentation (0.89 ± 0.02 % LAE) and GTY at the end of the storage period (0.99 ± 0.03 % LAE). All yogurts maintained high viable counts of yogurt bacteria throughout the storage period with higher Lactobacillus spp. counts for tea yogurts (6.27 - 7.03 log CFU/ml) compared to plain yogurt (6.08 - 6.54 log CFU/ml). Streptococcus thermophilus counts increased in all yogurts during the first week of storage. LCMS analysis revealed the absence of several phenolic compounds in yogurts, despite their presence in tea water extracts, as well as the presence of new phenolic compounds, iv suggesting possible tea polyphenol metabolism by yogurt bacteria. Tea can be used to enhance the antioxidant properties and sustain viable yogurt bacteria during refrigerated storage.